Heat Stress in Iraq Slashes Dairy Cow Health and Milk Production: Stres Panas di Irak Pangkas Kesehatan Sapi Perah dan Produksi Susu - Azhar Lateef Shwish (Academia Open, 2024)
This study examined the impact of heat stress on dairy cows in Iraq, categorizing them into Comfortable Zone (CZ), Mild Stress (MS), and High Stress (HS) based on the Thermal Humidity Index (THI). Over 90 days, cows were monitored for physiological, hematological, biochemical, and milk production parameters. Results showed that as heat stress increased, cows exhibited higher respiration, heart, and pulse rates, and rectal and skin temperatures. Hemoglobin and packed cell volume decreased, while red blood cell count and other related measures increased. Biochemical analyses revealed higher levels of cortisol, blood urea nitrogen, total protein, and liver enzymes, with reduced albumin. Milk yield and quality significantly declined under HS conditions. These findings highlight the need for effective heat stress mitigation to protect cow health and dairy productivity in hot climates. Highlights: Heat Stress Impact: Increased respiration, heart, pulse rates, and rectal and skin temperatures. Blood Changes: Lower hemoglobin, higher cortisol, blood urea nitrogen, liver enzymes. Milk Production: Reduced yield, fat content, and protein content under high stress. Keywords: heat stress, dairy cows, physiology, milk production, Iraq